Amyloid β influences the relationship between cortical thickness and vascular load. Issue 1 (17th April 2020) - Parker, Thomas D.; Cash, David M.; Lane, Christopher A.; Lu, Kirsty; Malone, Ian B.; Nicholas, Jennifer M.; James, Sarah‐Naomi; Keshavan, Ashvini; Murray‐Smith, Heidi; Wong, Andrew; Buchanan, Sarah M.; Keuss, Sarah E.; et al.
Abstract: Introduction: Cortical thickness has been proposed as a biomarker of Alzheimer's disease (AD)– related neurodegeneration, but the nature of its relationship with amyloid beta (Aβ) deposition and white matter hyperintensity volume (WMHV) in cognitively normal adults is unclear. Methods: We investigated the influences of Aβ status (negative/positive) and WMHV on cortical thickness in 408 cognitively normal adults aged 69.2 to 71.9 years who underwent 18 F‐Florbetapir positron emission tomography (PET) and structural magnetic resonance imaging (MRI). Two previously defined Alzheimer's disease (AD) cortical signature regions and the major cortical lobes were selected as regions of interest (ROIs) for cortical thickness. Results: Higher WMHV, but not Aβ status, predicted lower cortical thickness across all participants, in all ROIs. Conversely, when Aβ‐positive participants were considered alone, higher WMHV predicted higher cortical thickness in a temporal AD‐signature region. Discussion: WMHV may differentially influence cortical thickness depending on the presence or absence of Aβ, potentially reflecting different pathological mechanisms.